2023
DOI: 10.3390/toxins15020166
|View full text |Cite
|
Sign up to set email alerts
|

Role of Urological Botulinum Toxin-A Injection for Overactive Bladder and Voiding Dysfunction in Patients with Parkinson’s Disease or Post-Stroke

Abstract: Botulinum toxin A (BoNT-A) paralyzes muscle by blocking acetylcholine release at the synaptic junction. BoNT-A has shown its therapeutic effects in neurological disorders such as Parkinson’s disease (PD) and post-stroke spasticity. A high proportion of patients with PD and post-stroke develop neurogenic detrusor overactivity (nDO) and then develop urinary incontinence and overactive bladder (OAB) symptoms. This study aimed to disclose the safety and efficacy of BoNT-A injection in treating bladder and voiding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 72 publications
(109 reference statements)
0
7
0
Order By: Relevance
“…There are several reports on the treatment outcome of BoNT-A on neurogenic OAB. Satisfactory outcomes were also noted in patients with PD and OAB [ 26 ] and in men with persistent OAB symptoms after transurethral resection of the prostate [ 27 ]. Overall, among patients with OAB, older adults who are frail or who have OAB due to chronic CNS disorders can attain the same treatment results as younger patients and older adults without frailty, including significant improvement of OAB symptoms and quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several reports on the treatment outcome of BoNT-A on neurogenic OAB. Satisfactory outcomes were also noted in patients with PD and OAB [ 26 ] and in men with persistent OAB symptoms after transurethral resection of the prostate [ 27 ]. Overall, among patients with OAB, older adults who are frail or who have OAB due to chronic CNS disorders can attain the same treatment results as younger patients and older adults without frailty, including significant improvement of OAB symptoms and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Suburothelial BoNT-A injection at a dose of 200 U increased bladder capacity and improved the incontinence grade in patients with spinal cord lesions or multiple sclerosis, but only small case series support BoNT-A injection for NDO in patients with PD or CVA [ 30 ]. Most researchers would like to manage PD and poststroke patients using BoNT-A 100 U intradetrusor injection to achieve long-term efficacy and reduce adverse effects [ 26 ]. After BoNT-A injection, 79.2% of patients with PD and OAB reported an improvement in OAB symptoms, 29.1% experienced resolution of UUI while their PVR increased, and 12.5% of the patients required CIC [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some cerebrovascular diseases such as stroke can lead to OAB. After the acute phase of stroke, OAB is the main lower urinary tract symptom in post-stroke patients ( 31 ). Akkoç et al found that post-stroke patients experienced urinary urgency in about two-thirds of patients at 6-month follow-up ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in the treatment of OAB with BoNT, it is important to note that its action is not solely attributed to muscle relaxation but also involves blocking sensitive receptors [ 36 ]. Currently, the injection of BoNT/A is approved by the FDA as a third-line therapy for OAB [ 37 ]. Studies have shown that BoNT/A therapy leads to significant improvements in urinary symptoms for up to 12 weeks [ 38 ].…”
Section: Clinical Use Of Bontsmentioning
confidence: 99%